Research Bugis-Makassar vs Padang Pariaman (Between Panai Money and Bajapuik Customs) - Musrayani Usman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The amount of the dowry and process causes of conflict in Bugis and Padang Pariaman traditional marriages and what values can be exchanged. This type of research is qualitative using a field research approach and historical and analysed using N-Vivo R1, ten informants involved. informants are representatives to answer the formulation of the problem. Based on the results of research, especially in the Bugis-Makassar community, disagreements will cause negative things such as marriages can be cancelled, debts, elopement, pregnancy out of wedlock and suicide, while in the Padang Pariaman community where the tradition of the woman giving some money to the man-men, and the men will do a manjalang event to change the dowry and the amount is more. The conclusion of the research in this process is that the potential for conflict that occur will be greater, due to differences in social status and the need for meaning of economic values.